Evaluation of cardiac indices using M-mode echocardiography after administration of metoclopramide and ondansetron in donkeys (Equus asinus): an experimental study - Marzok, Mohamed; Kandeel, Mahmoud; Alkhodair, Khaled; Abdel-Raheem, Sherief; Ismail, Hisham; Farag, Alshimaa; Ibrahim, Hossam; El-Ashkar, Maged; Shousha, Saad; El-Khodery, Sabry (Frontiers in Veterinary Science, 2023)
The present study aimed to evaluate the cardiac indices using M-mode echocardiography after administration of metoclopramide and ondansetron in donkeys. For this purpose, ten apparently healthy Egyptian Baladi donkeys (Equus asinus) were used in a cross-over prospective study. Two trials were conducted including the administration of metoclopramide hydrochloride anhydrous at a dose of 0.25 mg Kg-1 and ondansetron hydrochloride sodium at a dose of 0.15 mg Kg-1. For the control group (placebo), a total volume of 50 ml of isotonic saline 0.9% was administered. Echocardiographic examination was carried out using Digital Color Doppler Ultrasound System equipped with 2 to3.9 MHz phased array sector scanner transducer. In general, the fractional shortening (FS%) was significantly affected by the time for metoclopramide (P = 0.031) and ondansetron (P= 0.047) compared with those of placebo. where treatment with metoclopramide provoked significantly higher percentages of FS % at T60 (P = 0.009), and T90 (P = 0.028) compared with those for ondansetron and placebo. Interaction of time x treatment also showed a statistically significant alteration of FS% (P< 0.05) while the values were rebounded to the basal line at T240. Metoclopramide induced a significant decrease of E-point to septal sepa¬ration (EPSS) at T90 (P = 0.005), and T240 (P = 0.007) compared with ondansetron and placebo. Time x treatment interaction also showed a significant (P< 0.05) variation of EPSS, where the values were rebounded to the basal line at T300. Values of Mitral valve opening speed (DE SLP) were significantly affected by the time (P = 0.004) in the metoclopramide group compared with those of ondansetron and placebo. Administration of metoclopramide and ondansetron provoked significant alterations of DE SLP at T60 (P = 0.039), T120 (P = 0.036), and T300 (P = 0.005) compared with placebo. In conclusion, care should be taken when administering both treatments, especially in animals with suspected heart problems.